Исторический акционализм как методология исследования исторического процесса - Гавриленко, И. (Социология: теория, методы, маркетинг, 1999)
There has been presented a new research direction in sociology aimed to analyzehistorical process. Taking into account various theoretical models of historical process based on corresponding paradigms (Marxist, functional, conflictualist), theauthor has proved that the historic actionalism methodology would be the most fruitful and adequate for the current situation in Ukraine. If society is a system ofhistorical actions aimed to reform existing relations, then, with the help of presentedapproach, it can be analyzed like consensus and conflict interactions between allsocial subjects (groups, organizations, institutes) without exception.